Estimation of Soil Erosion Caused by Flash Floods Using MUSLE Method: The Case of Igneada (Kırklareli) Flash Flood (5.9.2023) - Emre Özşahin; Mikayil Öztürk (Doğal Afetler ve Çevre Dergisi)
A catastrophic flood occurred on 5.9.2023 due to extremely heavy rainfall in the river basins on the Black Sea catchment area of the Istranca Region in the Thracian Peninsula of Türkiye. As a result of these rainfalls, a catastrophic flash flood occurred on 5.9.2023. This flash flood, which caused severe soil erosion, also led to a heavy accumulation of mud in areas close to the valley floor in the lower basin where deposition in the rivers increased. According to official records, the impact of the flash flood was felt the most in the Degirmen river basin. In this study, it was aimed to estimate the soil erosion caused by the flash flood that occurred on 5.9.2023 in the Degirmen river basin. Thus, important information was obtained in terms of giving an idea about both the potential location and severity of this problem with dramatic consequences. The MUSLE model was preferred for the calculation of soil loss caused by flash floods and the creation of erosion risk maps. The model was applied using ArcGIS soil erosion tool based on Geographic Information Systems (GIS). As a result, it was determined that soil erosion caused by flash floods in the Degirmen river basin is mostly in the river valleys in the upper basin where the increase in slope and precipitation is significant, and its effect is in the areas close to the valley floor in the lower basin where deposition increases in the rivers. According to the MUSLE model results, 195,78 tons/day of sediment was estimated to have arrived at the time of the flash flood. The result of the study emphasize the importance of modeling soil erosion caused by flash floods at the scale of a lived event. Furthermore, the results of this study can be used to develop regional policies to address the real causes of soil erosion risk caused by flash floods.